Hydralazine, antinuclear antibodies, and the lupus syndrome. Issue 6320 (27th March 1982) - Mansilla-Tinoco, R; Harland, S J; Ryan, P J; Bernstein, R M; Dollery, C T; Hughes, G R; Bulpitt, C J; Morgan, A; Jones, J M
Abstract : The incidence of patients with positive antinuclear antibody test results rose during three years of treatment with hydralazine. At the end of that period over half of the patients (both rapid and slow acetylators) had titres exceeding 1/20, but the rate of rise was faster in the slow acetylators than in the rapid. There was a significant relation between the cumulative dose of hydralazine and the proportion of patients found to have antinuclear factors. Fewer black patients had positive test results than white. Patients whose antinuclear antibody test results changed fron negative to positive during the study showed this change five to 26 months after beginning treatment. Some patients showed a substantial fall in antinuclear antibody titre even though hydralazine was continued. From these findings patients in whom test results for antinuclear antibody became positive during treatment with hydralazine need not have the drug stopped unless they have clinical features of the lupus syndrome.